PERSEPSI KHALAYAK DALAM PENGGUNAAN MEDIA JEJARING SOSIAL UNTUK KAMPANYE POLITIK - Welly Wihayati (JURNAL SIGNAL, 2016)
The election campaign has largely been considered as an arena of the ongoing process of political communication, a very high intensity. The method used deskripsif qualitative research results: 1. The public perception regarding the use of social media for political campaigns in the city of Cirebon is still within reasonable limits to be used as a medium for political campaigns, if not deceive people, not against the law and is considered effective; 2.Barriers the use of social networking media for political campaigns that not all people taking social networking media, when there are pros and cons of social networking media occurs intimidate each other, there is even a menghacker, plowing, as if the candidates and vilify candidates candidate; 3. Supporting the use of social media for political campaigns, which will be a lot of followers, respect for the candidate, can raise funds, can perform community service, and even personal photos and daily activities can be updated, the status of building realized in the real world, and comment -komentar building.